Instrumental methods in food analysis (Elsevier, 1997)
Instrumental Methods in Food Analysis is aimed at graduate students in the science, technology and engineering of food and nutrition who have completed an advanced course in food analysis. The book is designed to fit in with one or more such courses, as it covers the whole range of methods applied to food analysis, including chromatographic techniques (HPLC and GC), spectroscopic techniques (AA and ICP), electroanalytical and electrophoresis techniques.